Wet spraying material for molten iron vessel and torpedo car coated with the same
Patent Information
- Application Number
- JP2023144800
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-18
AI Technical Summary
【0008】 本発明によれば、高炉スラグに対する耐久性に優れ、しかも施工後の耐用性にも優れる溶銑容器用の湿式吹付材及びそれを施工した混銑車を提供することができる。
Smart Images

Figure 2025037705000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a wet gunning material for a molten iron container and a torpedo car to which the same is applied. [Background technology]
[0002] A wet spraying material has long been known as a lining or repair material for various industrial kilns. In this method, water is added to a raw material mixture and the mixture is then pumped into a nozzle using air pressure, and a setting accelerator is added at or just before the nozzle and sprayed (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 63-265870 Summary of the Invention [Problem to be solved by the invention]
[0004] Wet gunning materials used in molten iron containers such as torpedo cars and molten iron ladles are naturally required to have resistance to penetration and corrosion by molten iron and blast furnace slag, particularly blast furnace slag, i.e., durability. However, according to tests and research by the present inventors, it has been found that in order to improve the durability of wet gunning materials used as linings or repair materials for molten iron containers after application, it is not sufficient to merely improve their durability against blast furnace slag, and new technical means are required.
[0005] The problem to be solved by the present invention is to provide a wet gunning material for a molten iron container which has excellent durability against blast furnace slag and also has excellent durability after application, and a torpedo car to which the same is applied. [Means for solving the problem]
[0006] According to the tests and researches by the inventors, it has been found that in order to improve the durability of the wet gunning material after application, it is necessary for the gunning material to have a property of expanding by a predetermined amount under a predetermined temperature and load. That is, the gunning material is often used for repairing the damaged parts of the bricks lining the molten iron vessel, and in such a case, the gunning material is subjected to the load of the bricks. If the gunning material shrinks under such a condition, it may cause the gunning material to peel off and damage the bricks, so it is necessary for the gunning material to have a tendency to expand under load. On the other hand, if the gunning material expands too much under load, it may cause damage to the bricks, so it is also required that the gunning material does not expand too much. From this perspective, the inventors conducted extensive analysis and research on actual applied bodies, taking into consideration the conditions of use of the applied bodies when the wet spraying material was applied, and found that if the expansion coefficient under a load of 0.20 MPa at 1200°C (hereinafter referred to as the "expansion coefficient under hot load") is within the range of 2.5±0.2%, and preferably within the range of 2.5±0.1%, peeling of the applied body and damage to the bricks are less likely to occur in the molten iron vessel, and as a result, the durability of the wet spraying material after application is improved. Furthermore, as a result of repeated testing and research by the inventors in order to achieve both a hot load expansion coefficient within the range of 2.5±0.2% and improved durability against blast furnace slag, they discovered that it is effective to use a zircon raw material having a particle size of less than 75 μm in combination with a silicon carbide raw material having a particle size of less than 75 μm, and thus completed the present invention.
[0007] That is, according to one aspect of the present invention, the following wet spray material is provided. A wet gunning material for a molten iron vessel, comprising a refractory raw material blend containing a zircon raw material having a particle size of less than 75 μm and a silicon carbide raw material having a particle size of less than 75 μm, and the balance containing mainly an alumina raw material, a silica raw material, and an alumina-silica raw material. A wet gunning material for a molten iron vessel, characterized in that the content of a zircon raw material having a particle size of less than 75 μm and a silicon carbide raw material having a particle size of less than 75 μm is 3 mass% or more and 17 mass% or less, respectively, based on 100 mass% of the refractory raw material mixture. According to another aspect of the present invention, there is provided a torpedo car to which the wet gunning material of the present invention has been applied. Effect of the Invention
[0008] According to the present invention, it is possible to provide a wet gunning material for a molten iron container which has excellent durability against blast furnace slag and also has excellent durability after application, and a torpedo car to which the same is applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The wet spray material of the present invention contains, based on 100 mass% of the refractory raw material mixture, 3 mass% to 17 mass% of zircon raw material having a particle size of less than 75 μm and 3 mass% to 17 mass% of silicon carbide raw material having a particle size of less than 75 μm. Here, the particle size in the present invention refers to the size of the sieve openings when the refractory raw material particles are sieved to separate them. For example, a zircon raw material having a particle size of less than 75 mm refers to a zircon raw material that passes through a sieve with openings of 75 μm, and a zircon raw material having a particle size of 75 μm or more refers to a zircon raw material that does not pass through a sieve with openings of 75 μm.
[0010] When a zircon raw material having a particle size of less than 75 μm (hereinafter referred to as "fine zircon raw material") is heated by contact with molten iron or slag during use of a molten iron vessel, it dissociates into zirconia and amorphous silica to generate a highly viscous glass phase. Then, when this glass phase is appropriately present around a silicon carbide raw material having a particle size of less than 75 μm (hereinafter referred to as "fine silicon carbide raw material"), durability against blast furnace slag is improved. That is, when the glass phase is appropriately present so as to cover the fine silicon carbide raw material, oxidation of the fine silicon carbide raw material is suppressed, and the inherent effect of the fine silicon carbide raw material in improving durability against blast furnace slag is fully exhibited. In addition, when both the zircon raw material and the silicon carbide raw material are fine raw materials having a particle size of less than 75 μm, the glass phase generated by dissociation of the fine zircon raw material is easily appropriately present around the fine silicon carbide raw material. This also fully exhibits the above-mentioned effect of improving durability against blast furnace slag. In the following description, durability against blast furnace slag is referred to as "slag durability."
[0011] If the content of the zircon fine raw material is less than 3% by mass, the glass phase is not generated sufficiently, and the effect of improving the durability of the slag cannot be obtained. On the other hand, if the content of the zircon fine raw material is more than 17% by mass, the glass phase is generated excessively, and the deformation under load becomes large. As a result, the specified expansion coefficient under hot load cannot be obtained. That is, while the expansion coefficient under hot load is required to be within the range of 2.5±0.2% as described above, if the content of the zircon fine raw material is more than 17% by mass, the expansion coefficient under hot load becomes less than 2.3%, and the durability of the applied body of the wet spraying material is reduced. In addition, if the content of the zircon fine raw material is more than 17% by mass, the hot strength of the applied body is also reduced, which also reduces the durability of the applied body. The content of the fine zircon raw material is preferably 3% by mass or more and 12% by mass or less.
[0012] In addition, when the content of the silicon carbide fine raw material is less than 3% by mass, the amount and number of the silicon carbide fine raw material are insufficient, and the effect of improving the durability of the slag cannot be obtained. On the other hand, when the content of the silicon carbide fine raw material is more than 17% by mass, the amount of fine particles in the construction body increases, and the deformation under load increases. Therefore, as in the case where the content of the zircon fine raw material is more than 17% by mass, the hot expansion coefficient under load is less than 2.3%, and the hot strength is also reduced, resulting in a decrease in the durability of the construction body. The content of the fine silicon carbide raw material is preferably 6 mass % or more and 12 mass % or less. Furthermore, in order to set the hot expansion coefficient under load within a preferred range of 2.5±0.1%, the total content of the fine zircon raw material and the fine silicon carbide raw material can be set to 15 mass % or more and 23 mass % or less.
[0013] The wet spraying material of the present invention preferably contains 8% by mass or more and 20% by mass or less of an alumina raw material having a particle size of less than 75 μm (hereinafter referred to as "fine alumina raw material") in 100% by mass of the refractory raw material mixture. The amorphous silica produced by dissociation of the fine zircon raw material is highly reactive. Therefore, if the fine alumina raw material is contained in the refractory raw material mixture, the fine alumina raw material reacts with the amorphous silica to produce mullite. Mullite has a high melting point of 1850°C and a high softening temperature under load, which contributes to improving hot strength and also contributes to suppressing melting loss and deformation under load. If the content of the fine alumina raw material is less than 8% by mass, the above-mentioned effect is not significant. On the other hand, if a large amount of the fine alumina raw material is contained, the thermal expansion coefficient increases, and there is a risk that the expansion coefficient under hot load will become excessive. For these reasons, the content of the fine alumina raw material is preferably 8% by mass or more and 20% by mass or less.
[0014] In the wet spraying material of the present invention, the remainder of the refractory raw material blend mainly contains an alumina raw material, a silica raw material, and an alumina-silica raw material. This is to ensure the alumina component that reacts with the zircon fine particle raw material, and the alumina and silica components for producing mullite. For example, one or more of alumina raw materials such as fused alumina, sintered alumina, bauxite, diaspore, aluminium shale, and calcined alumina, silica raw materials such as silica stone, silica sand, and amorphous silica (e.g., microsilica, silica flower, fumed silica, and white carbon), and alumina-silica raw materials such as phallosite, chamotte, clay, andalusite, sillimanite, kyanite, and mullite can be contained. The above refractory raw materials listed as the balance are "mainly" the balance, and the balance may include refractory raw materials other than the above refractory raw materials, binders such as Portland cement and alumina cement, and further dispersants, hardening regulators, thickeners, etc. Examples of refractory raw materials other than the above refractory raw materials include refractory raw materials generally used for refractories, such as pitch, magnesia, and carbon black, zircon raw materials having a particle size of 75 μm or more, and silicon carbide raw materials having a particle size of 75 μm or more.
[0015] In addition, in the wet gunning material of the present invention, it is preferable to add organic fibers in an amount of 0.05% by mass to 0.25% by mass. The organic fibers are burned away when heated due to contact with molten iron or slag during use of the molten iron container. The highly viscous glass phase generated by dissociation of the fine zircon raw material penetrates into the burned-away organic fibers, thereby contributing to improving the durability of the slag. The organic fibers also contribute to improving the explosion resistance of the applied structure. If the organic fiber content is less than 0.05% by mass, the above-mentioned effects are not significant. On the other hand, if a large amount of organic fiber is added, the density of the construction body decreases, and the slag durability and hot strength tend to decrease. For these reasons, it is preferable that the organic fiber content be 0.05% by mass or more and 0.25% by mass or less.
[0016] The wet spray material of the present invention is prepared by adding organic fibers as necessary to the above-mentioned refractory raw material mixture, further adding water and kneading the mixture, and then pumping the mixture to a nozzle by air pressure, adding a quick-setting agent at the nozzle or just before the nozzle, and spraying the mixture. Examples of the quick-setting agent include sodium silicate and lime. The quick-setting agent may be added to the refractory raw material mixture in advance, instead of adding it at the nozzle or just before the nozzle. EXAMPLES
[0017] The hot strength, hot expansion rate under hot load, and slag durability were evaluated for each example of wet gunning material shown in Table 1. In Table 1, "other refractory materials" mainly refers to binders, specifically alumina cement. The evaluation methods for hot strength, hot expansion rate under hot load, and slag durability are as follows.
[0018] <Hot strength> A specified amount of water was added to the raw material mixture of each example, and the mixture was kneaded, poured into a formwork, cured, and dried to obtain test pieces. The hot bending strength at 1450℃ was measured in accordance with JIS R2656:1995 "Test method for hot bending strength of firebricks and fire-resistant insulating bricks."
[0019] <Expansion rate under hot load> The raw material mixture of each example was mixed with a specified amount of water, poured into a mold, cured, and dried to obtain a test piece, which was previously fired at 1000°C for 3 hours. The test piece was attached to a differential load softening tester, and heated while applying a load of 0.20 MPa in accordance with JISR2209:2007 "Test method for load softening point of firebricks". The expansion coefficient under a load of 0.20 MPa at 1200°C, i.e., the hot load expansion coefficient, was calculated by measuring the height change of the test piece at 1200°C according to JISR2209:2007 "Test method for load softening point of firebricks". The hot load expansion coefficient was evaluated as follows: ◎ (excellent) when the deviation from the target value of 2.5% was 0.1% or less in absolute value, ◯ (good) when it was more than 0.1 and 0.2% or less, and × (unacceptable) when it was more than 0.2%.
[0020] <Slag durability> A specified amount of water was added to the raw material mixture of each example, and the mixture was kneaded, poured into a frame with a Φ50×50mm formwork set in the center of a Φ100×100mm mold, cured, and dried to obtain a crucible-shaped test specimen, which was previously fired at 1000°C for 3 hours. Blast furnace slag was placed in the test specimen, which was then placed in an electric furnace maintained at 1500°C and held there for 12 hours. The test specimen was then cut to determine the areas of the infiltrated and eroded parts. The composition of the blast furnace slag used was CaO: 43.4% by mass, SiO2: 39.7% by mass, FeO: 1.9% by mass, MgO: 9.2% by mass, and MnO2: 0.01% by mass. The slag durability was evaluated by setting the total area of the infiltrated part and the dissolved part in Comparative Example 1 as 100, and the relative value was evaluated as the slag durability index. Specifically, a slag durability index of less than 90 was rated as ⊚ (excellent), a slag durability index of 90 or more and less than 100 was rated as ◯ (good), and a slag durability index of 100 or more was rated x (unacceptable). In other words, the smaller the slag durability index, the more excellent the slag durability.
[0021] <Overall rating> Based on the above evaluation results, the specimens were rated on a three-level scale: ◎ (excellent), ○ (good), and × (unacceptable). Specifically, the specimens were rated as ◎ (excellent) when the hot bending strength was 1.7 MPa or more and both the evaluations of the hot expansion coefficient under load and the slag durability were ◎, as × (unacceptable) when at least one of the evaluations of the hot expansion coefficient under load and the slag durability was ×, and as ○ (good) in all other cases.
[0022] In the above evaluation method, the test pieces or specimens were prepared by pouring construction, but the inventors have confirmed that evaluation using test pieces or specimens prepared by pouring construction can be directly applied to evaluation of constructions made with wet sprayed materials.
[0023] [Table 1]
[0024] In Table 1, Examples 1 to 15 are wet gunning materials within the scope of the present invention. Both the hot expansion coefficient under load and the slag durability were good. Among them, Examples 5 to 7, 9, 10, 13, and 14, in which the total content of the fine zircon raw material and the fine silicon carbide raw material, the content of the fine alumina raw material, and the addition rate of the organic fiber were all within the above-mentioned preferred ranges, showed particularly good results in both the hot expansion coefficient under load and the slag durability, and also showed good results in the hot bending strength at 1450°C of 1.7 MPa or more.
[0025] Comparative Example 1 is an example in which the content of the fine zircon raw material is below the lower limit of the present invention, and the slag durability is reduced. On the other hand, Comparative Example 2 is an example in which the content of the fine zircon raw material is above the upper limit of the present invention, and the specified hot expansion coefficient under load is not obtained. In addition, the hot bending strength at 1450°C is also reduced. Comparative Example 3 is an example in which the content of the silicon carbide fine powder raw material is below the lower limit of the present invention, and the slag durability is reduced. On the other hand, Comparative Example 4 is an example in which the content of the silicon carbide fine powder raw material is above the upper limit of the present invention, and the desired hot expansion coefficient under load is not obtained. In addition, the hot bending strength at 1450°C is also reduced. In Comparative Example 5, the total content of the zircon fine raw material and the silicon carbide fine raw material was within the preferred range, but the content of the zircon fine raw material exceeded the upper limit of the present invention and the content of the silicon carbide fine raw material was below the lower limit of the present invention, resulting in reduced slag durability. In Comparative Example 6, the total content of the zircon fine raw material and the silicon carbide fine raw material was within the preferred range, but the content of the silicon carbide fine raw material exceeded the upper limit of the present invention, and the specified hot expansion coefficient under load was not obtained.
Claims
1. A wet gunning material for a molten iron vessel, comprising a refractory raw material blend containing a zircon raw material having a particle size of less than 75 μm and a silicon carbide raw material having a particle size of less than 75 μm, and the balance mainly containing an alumina raw material, a silica raw material and an alumina-silica raw material. A wet spraying material for a molten iron vessel, characterized in that the content of a zircon raw material having a particle size of less than 75 μm and a silicon carbide raw material having a particle size of less than 75 μm is 3 mass% or more and 17 mass% or less, respectively, in 100 mass% of a refractory raw material blend.
2. 2. The wet gunning material for a molten iron vessel according to claim 1, wherein the refractory raw material blend contains 8% by mass or more and 20% by mass or less of an alumina raw material having a particle size of less than 75 μm in 100% by mass of the refractory raw material blend.
3. 3. The wet gunning material for a molten iron vessel according to claim 1 or 2, wherein organic fibers are added in an amount of 0.05% by mass or more and 0.25% by mass or less based on 100% by mass of the refractory raw material blend.
4. 3. The wet gunning material for a molten iron vessel according to claim 1, wherein a total content of the zircon raw material having a particle size of less than 75 μm and the silicon carbide raw material having a particle size of less than 75 μm is 15 mass% or more and 23 mass% or less.
5. 3. The wet spraying material for a molten iron vessel according to claim 1 or 2, wherein a total content of a zircon raw material having a particle size of less than 75 μm and a silicon carbide raw material having a particle size of less than 75 μm is 15 mass% or more and 23 mass% or less, and an organic fiber is added in an amount of 0.05 mass% or more and 0.25 mass% or less relative to 100 mass% of the refractory raw material blend.
6. A torpedo car to which the wet gunning material for a molten iron container according to claim 1 or 2 has been applied.
Citation Information
Patent Citations
Refractory material for spraying
JP1988265870A